The Effectiveness of Laboratory Digitalization for 21st Century Learning - Sulistyo, Wahyu Djoko; Deny Yudo, Wahyudi; Azmi Bin Muhamad @Md., Jalani; Candra Kurnia, Putra; Hartono, (International Journal of Interactive Mobile Technologies (iJIM), 2024)
Learning resources are crucial and strategic elements that impact the accessibility of easy, fast, accurate, and affordable information in the era of Society 5.0. Learning resources must be adaptable to technological advancements. The history laboratory is a learning resource that must be transformed and adapted to address the aforementioned needs and problems as a solution. The extensive collection of owned items has the potential to support this. This paper describes the creation of a digital laboratory by utilizing collections from the UM History Department. The research employed the Research and Development (R&D) method, utilizing the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The study presents findings on the importance of digitizing laboratories as educational resources and digital laboratory products for the UM History Department. This digital laboratory product consists of several features, including an e-book (book catalog), an e-repository (final project catalog), an e-museum (museology collection catalog), tool lending, and graduate assessment. The results of the validation and implementation tests demonstrate that the criteria are highly valid and extremely effective. These results demonstrate that the digital laboratory serves as a more effective and efficient learning resource that is easily accessible and usable for civil society 5.0.